Investigation of electron acceptor states in poly(3-methylthiophene) - Taylor, D. M. (2015)
Both the DC and AC admittance of Schottky barrier diodes formed at the interface of aluminium and poly(3-methyl thiophene) have been investigated in some detail. The capacitance-voltage plots for the devices suggest the presence of two acceptor states, one shallow and one deep. The total concentration of acceptor states, 10 24-10 26 m -3 depending on the degree of undoping, agrees well with estimates from the reverse I-V characteristics assuming image force lowering of the interfacial potential barrier.